The Effect of Price and Lifestyle on Consumer Satisfaction with Thrifting Products Among Faculty of Economics and Business Students at Mataram University - Ni Putu Wulandari; Weni Retnowati (Indonesian Development Economics and Localities, 2026)
This study aims to examine the effect of Price and Lifestyle on Consumer Satisfaction on Thrifting Products among Faculty of Economics and Business (FEB) Students at Mataram University. The population in this study were all FEB students at Mataram University. The number of samples in this study was 100 respondents with a sampling technique using non-probability sampling with a purposive sampling method. Data analysis used was Multiple Linear Regression to prove the research hypothesis. Data that had met the validity test, reliability test and classical assumption test were then processed to obtain a regression equation. The data analysis technique used the SPSS Version 30 Program. Based on the results of the data analysis, it was found that Price (X1) had a positive and significant effect on Consumer Satisfaction (Y) on Thrifting Products, with a regression coefficient value of 0.182 and obtained a calculated t value greater than the t table (2.077 > 1.985) with a significance of 0.040 < 0.05. Lifestyle (X2) has a positive and significant effect on Consumer Satisfaction (Y) for Thrifting Products, with a regression coefficient value of 0.495 and a calculated t-value greater than the t-table (6.241 > 1.985) with a significance of 0.001 < 0.05.